The impact of suicide prevention training for nursing assistant students: Knowledge and willingness to intervene - Mette Valdersdorf Jensen; Stine Bojen Aagaard Frandsen; Katrine Ulrikke Madsen; Lena Rossen Østergaard; Christina Petrea Larsen; Erik Christiansen (PLoS ONE, 2025)
Nursing assistants frequently encounter individuals at risk of suicidal behavior in various healthcare settings. This study aims to assess the impact of suicide prevention training materials on nursing assistant students’ knowledge of, and willingness to intervene in suicidal behavior. Pre- and post-training assessments were conducted using the Revised Facts on Suicide Quiz and the Willingness to Intervene against Suicide Questionnaire measuring students’ knowledge of and willingness to intervene in suicidal behavior. Repeated measures analyses were used to assess changes before and after the use of teaching materials. Students significantly improved overall scores on the Revised Facts on Suicide Quiz (from a pretest mean of 9.55 ± 2.97 to a posttest mean of 13.28 ± 2.51, (p < .001) and the Willingness to Intervene against Suicide Questionnaire (from a pretest mean of 85.63 ± 8.22 to a posttest mean of 92.28 ± 8.93, (p < .001.). Attitudes were not a significant predictor of intention to intervene. These findings underscore the importance of training nursing assistants in suicide prevention as a means of early intervention of suicide behavior. Fostering a proactive attitude and willingness to intervene is crucial for nursing assistants in early identification and intervention in cases of suicidal behavior within healthcare settings. Finally, the results underscore the importance of targeted suicide prevention curricula in social and health-related vocational programs.